Estudo da atividade antimicrobiana do óxido de cobre dopado com zinco - Cabral, Leticia Cristina Apostolico (2022)
With the rapid spread of bacterial resistance, bacterial infections, especially antibioticresistant infections, become a major problem for human bacterial health. Thus, the antimicrobial activity towards metals and metal oxides has been increasingly explored in recent years, where metal oxides can simultaneously induce cell destruction by cell walls and intracellular targets through physical interactions, ion release and generation of reactive oxygen species, which makes it harder for bacteria to develop resistance. Considering this, this study proposes to correlate the influence of the amount of zinc and the calcination temperature on the antimicrobial activity. In the synthesis of the metallic precursor resin, a molar ratio of ethylene glycol/citric acid/metal (8/2/1 mol) was used, with different amounts of zinc (2.5, 5.0 and 10.0%). To obtain the metallic oxide, the resulting resin was calcined at 300 and 400 ºC for 120 minutes. The antimicrobial activity was first tested in a trial test, where strains 090 and 051 of E. coli were tested and the one with the best inhibition result (051) passed to the minimum inhibitory concentration stage, showing bactericidal and bacteriostatic activity, where the minimum inhibitory concentration presented was 6g/L for Zn 2.5% 8g/L for Cu 100% both at 300ºC and for 400ºC the result was 2g/L for Zn 10% and 6g/L for Cu 100% observing the influence of calcination temperature and zinc doping on the results.